The emerging role and clinical significance of circRNAs in papillary thyroid cancer - Ma, Jing; Xu, Jing; Zhang, Xiaoqi; Quan, Jinxing (Frontiers in Endocrinology, 2024)
Papillary thyroid cancer (PTC) is the most common type of thyroid malignancy, and its global incidence has been gradually increasing. For advanced PTC, the mortality rates are also increasing yearly. Despite advancements in diagnosis and treatment, some advanced PTC exhibit aggressive behaviors, leading to a poor prognosis.CircRNAs are a class of non-coding RNAs characterized by a covalently closed loop structure. Their stability and abundance have positioned them as promising diagnostic and prognostic biomarkers. Numerous studies have identified dysregulated circRNAs in PTC tissues and cell lines, suggesting their involvement in PTC initiation and progression. In this review, we provide an overview of circRNAs and systematically discuss their role in PTC. CircRNAs affect cancer progression by regulating the Wnt/β-catenin, PI3K/AKT, MAPK pathways, and others. Furthermore, circRNAs have been implicated in PTC metastasis and chemoresistance. We highlight their potential value as diagnostic markers, therapeutic targets, and prognostic indicators.In conclusion, circRNAs play a critical role in PTC, and dysregulated circRNAs influence multiple signaling pathways and cellular processes involved in tumorigenesis and metastasis. It represents a promising avenue for advancing the diagnosis, management, and treatment of PTC.